2018
DOI: 10.4103/aer.aer_48_18
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia during labor: Attitudes among expectant mothers and their care providers

Abstract: Introduction:Varying levels of knowledge and attitudes among parturients and physicians toward epidural analgesia result in its low utilization. We aimed to assess the knowledge, attitude, and practice of parturients, obstetricians, and anesthesiologists regarding epidural labor analgesia.Methodology:We surveyed obstetricians, anesthesiologists, and parturients availing care and later delivered at our hospital from July 1, 2017, to December 31, 2017. Knowledge, attitude, and practice regarding epidural analges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
2
9
1
1
Order By: Relevance
“…The use of epidural anesthesia is not universal around the World. In India for example the knowledge, attitude, and practice regarding epidural anesthesia among parturient women are different [ 39 ]. Kamakshi found that about 33% of the participants knew that delivery is possible without pain, but only 18% were satisfied with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of epidural anesthesia is not universal around the World. In India for example the knowledge, attitude, and practice regarding epidural anesthesia among parturient women are different [ 39 ]. Kamakshi found that about 33% of the participants knew that delivery is possible without pain, but only 18% were satisfied with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There is a known gap between the desire for labor using analgesia and its availability as well as poor knowledge about epidural analgesia among women. This can also lead to its low utilization during labor 26 …”
Section: Discussionmentioning
confidence: 99%
“…Negative experiences were reported by women in regard to miscommunication with care providers with lack of empathy from the clinicians, late provision of epidural analgesia due to anaesthetist availability and subsequent ineffective analgesia during the second stage of labour (Attanasio et al., 2015). Timely epidural anaesthesia may not always be provided due to service and anaesthetist availability (Kamakshi et al., 2018). For women to be empowered in their pain relief decision‐making, midwives need to provide ‘open communication, adequate life skills, a nurturing and caring environment and a democratic management structure’ (Too, 1996:44).…”
Section: Discussionmentioning
confidence: 99%